"Going up?" A sport psychology consultant's guide to the elevator speech. Issue 2 (3rd May 2016) - Simpson, Duncan
ABSTRACT: Professionals should be able to give a clear and concise summary of their work irrespective of their occupation. As sport psychology is still a growing field, consultants need to be able to educate potential clients (e.g., athletes, coaches, and parents) about their work as well as develop methods to promote the use of their services. One strategy that SPCs can use to educate and promote the benefits of sport psychology services is the elevator speech. The term elevator speech originates from the business world and refers to a short 30–60 sec persuasive speech (Daum, 2013 ). Popular media outlets have provided numerous suggestions on how to construct an effective elevator speech, but these suggestions are not tailored to the field of sport psychology. Thus, the purpose of the present article is to propose different methods of constructing elevator speeches to educate and engage three possible clientele groups for sport psychology consultants: (a) athletes, (b) coaches, and (c) parents.